The Location-Scale Mixture Exponential Power Distribution: A Bayesian and Maximum Likelihood Approach. (9th October 2012) - Rahnamaei, Z.; Nematollahi, N.; Farnoosh, R.
Abstract : We introduce an alternative skew-slash distribution by using the scale mixture of the exponential power distribution. We derive the properties of this distribution and estimate its parameter by Maximum Likelihood and Bayesian methods. By a simulation study we compute the mentioned estimators and their mean square errors, and we provide an example on real data to demonstrate the modeling strength of the new distribution.